Laminate body for fuel battery

JP2025020751APending Publication Date: 2025-02-13SUMITOMO RIKO CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023124324
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-31
Publication Date
2025-02-13

AI Technical Summary

Benefits of technology

【0012】 本発明によれば、優れた耐酸接着性を示す燃料電池用の積層体を提供できる。 とりわけ、高温かつ長期間の条件下における耐酸接着性に優れる燃料電池用の積層体を提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025020751000001_ABST
    Figure 2025020751000001_ABST
Patent Text Reader

Abstract

To provide a laminate body for a fuel battery with an excellent acid-resistant adhesion under a high-temperature and long-term condition.SOLUTION: The laminate body is formed by making a separator 5 as a base material and a lip 4b as a seal member attach to each other by an adhesive layer 6, the lip 4b being formed of a rubber composition including the following component (A), the adhesive layer 6 being formed of an adhesive including the following components (α) and (β), the component (A) being a rubber component formed of at least one of ethylene-propylene-diene rubber and ethylene-butene-diene rubber, the component (α) being a copolymer oligomer type of silane coupling agent having a specific hydrophilic functional group and a specific hydrophobic functional group in a specific ratio, and the component (β) being an organic titanate compound.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminate for a fuel cell in which a base material and a sealing member are bonded via an adhesive layer, and more particularly to a laminate for sealing a fuel cell in which a base material for a fuel cell, such as a metal separator, and a rubber sealing member are bonded via an adhesive layer. [Background technology]

[0002] Fuel cells, which generate electricity through electrochemical reactions of gases, have high power generation efficiency, emit clean gases, and have very little impact on the environment. Among them, solid polymer fuel cells can be operated at relatively low temperatures and have a high output density. For this reason, they are expected to be used in a variety of applications, including power generation and as a power source for automobiles.

[0003] In a polymer electrolyte fuel cell, a cell in which a membrane electrode assembly (MEA) and the like are sandwiched between separators (separators made of metal or the like) is a power generation unit. The MEA is composed of a polymer membrane (electrolyte membrane) that serves as an electrolyte, and a pair of electrode catalyst layers [a fuel electrode (anode) catalyst layer, an oxygen electrode (cathode) catalyst layer] arranged on both sides of the electrolyte membrane in the thickness direction. A porous layer (gas diffusion layer) for diffusing gas is further arranged on the surface of the pair of electrode catalyst layers. A fuel gas such as hydrogen is supplied to the fuel electrode side, and an oxidant gas such as oxygen or air is supplied to the oxygen electrode side. Electricity is generated by an electrochemical reaction at the three-phase interface between the supplied gas, the electrolyte, and the electrode catalyst layer. A polymer electrolyte fuel cell is constructed by stacking a number of the above-mentioned cells into a cell stack, which is fastened by end plates or the like arranged on both ends in the cell stacking direction.

[0004] The separators are provided with flow paths for gases supplied to the electrodes and for coolants to reduce heat generation during power generation. The electrolyte membrane is proton conductive when it contains water, and therefore must be kept wet during operation. In order to prevent gas mixing and gas and coolant leakage and to keep the inside of the cell wet, it is important to ensure sealing around the MEA and porous layer and between adjacent separators, and therefore sealing members (gaskets) are required to seal the above locations.

[0005] The sealing member is also exposed to water produced during power generation. This water contains sulfonic acid and the like that has eluted from the electrolyte membrane, so the adhesion of the sealing member to the separator is required to be acid-resistant.

[0006] From the viewpoint of improving acid-resistant adhesion, the applicant has already proposed a laminate for a fuel cell in which a separator and a sealing member are bonded via an adhesive layer made of a specific adhesive (Patent Document 1). Such a laminate for a fuel cell is a copolymer oligomer type having a specific hydrophilic functional group and a specific hydrophobic functional group, and exhibits good acid-resistant adhesion by using an adhesive containing a silane coupling agent in which the molar ratio (Ma / Mb) of the amount of substance Ma (mol) of the hydrophilic functional group to the amount of substance Mb (mol) of the hydrophobic functional group contained in 1 mole of the molecule is within a specific range. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] International Publication No. 2022 / 208926 Summary of the Invention [Problem to be solved by the invention]

[0008] Although the laminate for fuel cells described in Patent Document 1 exhibits good acid-resistant adhesion, in recent years there has been a tendency for power generation temperatures to rise in order to improve power generation efficiency, and new technological developments are required to improve the acid-resistant adhesion between the substrate and the sealing member so that good adhesion can be obtained even under more severe conditions.

[0009] The present invention has been made in view of the above circumstances, and provides a laminate for a fuel cell, which exhibits excellent acid-resistant adhesion. [Means for solving the problem]

[0010] As a result of extensive research to solve the above problems, the inventors have discovered that by using an adhesive that combines a specific silane coupling agent and an organic titanate compound as an adhesive for bonding a substrate and a sealing member made of a specific rubber composition, it is possible to improve the acid-resistant adhesion between the substrate and the sealing member, and to demonstrate excellent acid-resistant adhesion even under high-temperature and long-term conditions.

[0011] That is, the gist of the present invention is the following [1] to [4]. [1] A laminate for a fuel cell comprising a substrate and a sealing member bonded together via an adhesive layer, the sealing member being made of a rubber composition containing the following component (A), and the adhesive layer being made of an adhesive containing the following components (α) and (β): (A) At least one of an ethylene-propylene-diene rubber and an ethylene-butene-diene rubber. (α) A copolymer oligomer type silane coupling agent having a hydrophilic functional group and a hydrophobic functional group, wherein the hydrophilic functional group is the following (a) and the hydrophobic functional group is the following (b), and the molar ratio (Ma / Mb) of the amount of substance Ma (mol) of the hydrophilic functional group to the amount of substance Mb (mol) of the hydrophobic functional group contained in 1 mole of the molecule is 0.33 to 3.00. (a) At least one selected from the group consisting of a silanol group, an alkoxy group, an amino group, an isocyanate group, an epoxy group, a ureido group, a carboxy group, and a hydroxy group, and contains at least a silanol group or an alkoxy group. (b) At least one selected from the group consisting of a vinyl group, a (meth)acryloyl group, a maleimide group, a methyl group, an ethyl group, a styryl group, a phenyl group, and a mercapto group. (β) Organic titanate compounds. [2] The laminate for a fuel cell according to [1], wherein the component (β) in the adhesive is at least one of a titanium alkoxide and a titanium chelate. [3] The laminate for a fuel cell according to [1] or [2], wherein the blending amount of the component (β) in the adhesive is 0.5 to 200 parts by mass per 100 parts by mass of the component (α). [4] The laminate for a fuel cell according to any one of [1] to [3], wherein the substrate is made of austenitic stainless steel. Effect of the Invention

[0012] According to the present invention, it is possible to provide a laminate for a fuel cell that exhibits excellent acid-resistant adhesion. In particular, it is possible to provide a laminate for a fuel cell that has excellent acid resistance and adhesion even under high temperature and long-term conditions. [Brief description of the drawings]

[0013] [Figure 1] 1 is a cross-sectional view showing an example of a laminate for a fuel cell according to the present invention. [Diagram 2] 1 is a cross-sectional view showing an example of a fuel cell seal body using a laminate for a fuel cell according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Next, an embodiment of the present invention will be described in detail, although the present invention is not limited to this embodiment. In this specification, the term "(meth)acryloyl group" refers to an acryloyl group or a methacryloyl group, and the term "(meth)acrylate" refers to an acrylate or a methacrylate.

[0015] A laminate for a fuel cell according to one embodiment of the present invention (hereinafter sometimes referred to as "the laminate for a fuel cell") is a laminate for a fuel cell formed by bonding a substrate and a sealing member via an adhesive layer, characterized in that the sealing member is made of a rubber composition (hereinafter sometimes referred to as "the rubber composition") containing the following component (A), and the adhesive layer is made of an adhesive containing the following components (α) and (β). (A) At least one of an ethylene-propylene-diene rubber and an ethylene-butene-diene rubber. (α) A copolymer oligomer type silane coupling agent having a hydrophilic functional group and a hydrophobic functional group, wherein the hydrophilic functional group is the following (a) and the hydrophobic functional group is the following (b), and the molar ratio (Ma / Mb) of the amount of substance Ma (mol) of the hydrophilic functional group to the amount of substance Mb (mol) of the hydrophobic functional group contained in 1 mole of the molecule is 0.33 to 3.00. (a) At least one selected from the group consisting of a silanol group, an alkoxy group, an amino group, an isocyanate group, an epoxy group, a ureido group, a carboxy group, and a hydroxy group, and contains at least a silanol group or an alkoxy group. (b) At least one selected from the group consisting of a vinyl group, a (meth)acryloyl group, a maleimide group, a methyl group, an ethyl group, a styryl group, a phenyl group, and a mercapto group. (β) Organic titanate compounds.

[0016] The laminate for fuel cells in Patent Document 1, which is the above-mentioned prior art, exhibited good acid-resistant adhesion after, for example, immersion in a 90°C aqueous sulfuric acid solution (pH=3.0) for 168 hours or 336 hours, but in some cases, for example, under harsher conditions such as a higher temperature environment or for a longer period of time, there is room for improvement in the acid-resistant adhesion. For example, the laminate for fuel cells in Patent Document 1 has room for improvement in acid-resistant adhesion after immersion in a 120°C aqueous sulfuric acid solution (pH=3.0) for 336 hours, which is a harsher condition.

[0017] The present fuel cell laminate can maintain good acid-resistant adhesion even under harsh conditions such as higher temperature environments and long periods of time. For example, the present fuel cell laminate exhibits good acid-resistant adhesion even after immersion in a sulfuric acid aqueous solution (pH=3.0) at a high temperature of 120° C. for a long period of time of 336 hours, and therefore can further improve adhesion reliability compared to conventional techniques.

[0018] Furthermore, the present fuel cell laminate surprisingly exhibits good acid-resistant adhesion even after immersion for an even longer period of time, for example, 672 hours in an aqueous sulfuric acid solution (pH = 3.0) at 120°C, thereby dramatically improving adhesion reliability compared to conventional techniques. In particular, when, for example, titanium alkoxide is used as the organic titanate compound (β) to be blended in the adhesive layer of the present fuel cell laminate, the laminate exhibits good acid-resistant adhesion even after immersion in, for example, an aqueous sulfuric acid solution (pH=3.0) at 120°C for an even longer period of 840 hours, and is therefore particularly useful. The sealing member, adhesive layer, and substrate that constitute the present laminate for a fuel cell will be described below.

[0019] <Sealing material> First, each material of the rubber composition for forming the seal member will be described.

[0020] <Rubber component (A)> As the rubber component (A), at least one of ethylene-propylene-diene rubber (EPDM) and ethylene-butene-diene rubber (EBT) is used. From the viewpoint of further improving the acid-resistant adhesion of the sealing material, particularly the acid-resistant adhesion under high temperature and long-term conditions, and from the viewpoint of sealability, it is preferable to use EBT as the rubber component (A).

[0021] The diene amount (mass proportion of the diene component) of EPDM and EBT is, for example, preferably in the range of 3.0 to 15 mass %, and more preferably in the range of 3.5 to 14.5 mass %.

[0022] The diene component of EPDM and EBT is preferably, for example, a diene monomer having 5 to 20 carbon atoms. Specific examples thereof include 1,4-pentadiene, 1,4-hexadiene, 1,5-hexadiene, 2,5-dimethyl-1,5-hexadiene, 1,4-octadiene, 1,4-cyclohexadiene, cyclooctadiene, dicyclopentadiene (DCP), 5-ethylidene-2-norbornene (ENB), 5-vinyl-2-norbornene (VNB), 5-butylidene-2-norbornene, 2-methallyl-5-norbornene, and 2-isopropenyl-5-norbornene.

[0023] The ethylene content of the EPDM (mass proportion of the ethylene component) is, for example, preferably in the range of 35 to 50 mass%, more preferably in the range of 40 to 50 mass%, and the propylene content (mass proportion of the propylene component) is, for example, preferably in the range of 42 to 55 mass%, more preferably in the range of 44 to 50 mass%.

[0024] The ethylene content (mass proportion of the ethylene component) of EBT is, for example, preferably in the range of 35 to 55 mass%, more preferably in the range of 40 to 53 mass%, and the butene content (mass proportion of the butene component) is, for example, preferably in the range of 35 to 55 mass%, more preferably in the range of 38 to 50 mass%.

[0025] The rubber component (A) is the main component of the rubber composition and usually accounts for 40% by mass or more of the entire rubber composition. The amount of the rubber component (A) is, for example, preferably in the range of 40 to 80% by mass, more preferably in the range of 45 to 75% by mass, of the entire rubber composition.

[0026] In addition to the rubber component (A), the rubber composition may contain various additives that are typically used in rubber compositions, such as plasticizers, fillers, crosslinking agents (organic peroxides, etc.), crosslinking assistants, and antioxidants.

[0027] Plasticizers Examples of the plasticizer include petroleum-based plasticizers such as process oil, lubricating oil, paraffin, liquid paraffin, and Vaseline, fatty oil-based plasticizers such as castor oil, linseed oil, rapeseed oil, and coconut oil, waxes such as tall oil, sab, beeswax, carnauba wax, and lanolin, linoleic acid, palmitic acid, stearic acid, and lauric acid, which may be used alone or in combination of two or more.

[0028] The amount of the plasticizer is usually 60 parts by mass or less, preferably 5 to 50 parts by mass, and more preferably 8 to 40 parts by mass, based on 100 parts by mass of the rubber component (A). The amount of the plasticizer may be in the range of 10 to 30 parts by mass, or 10 to 25 parts by mass, based on 100 parts by mass of the rubber component (A).

[0029] Among the plasticizers, a plasticizer having a pour point of -30°C or less is preferred, and a plasticizer having a pour point of -40°C or less is more preferred. Examples of such plasticizers include poly-α-olefin, dioctyl phthalate (DOP), dioctyl adipate (DOA), dioctyl sebacate (DOS), dibutyl sebacate (DBS), and the like. These may be used alone or in combination of two or more. Among them, poly-α-olefin is preferred from the viewpoint of good compatibility with the rubber component (A) and resistance to bleeding. Poly-α-olefin is a polymer of α-olefins having 6 to 16 carbon atoms. In poly-α-olefins, the smaller the molecular weight, the lower the viscosity and the lower the pour point.

[0030] As described above, the lower the pour point of a plasticizer, the less likely it is to harden at extremely low temperatures. Therefore, the lower the pour point of a plasticizer, the greater the effect of suppressing crystallization of the rubber component at extremely low temperatures. On the other hand, if the pour point is too low, it is likely to volatilize during operation of the fuel cell, etc. Therefore, it is desirable for the pour point of the plasticizer to be -80°C or higher. The pour point can be measured in accordance with JIS K 2269 (1987).

[0031] The kinetic viscosity of the plasticizer at 40° C. is preferably 8 to 500 mm 2 / s, more preferably 9 to 460 mm 2 / s range. In other words, when a plasticizer showing such a kinetic viscosity is used, it has good compatibility with rubber and low volatility, and therefore has excellent compression set properties (low settling properties). The kinetic viscosity of the plasticizer is measured in accordance with JIS K 2283.

[0032] Filler Examples of the filler include carbon black and silica. These may be used alone or in combination of two or more. The grade of the carbon black is not particularly limited, and examples thereof include SAF grade, ISAF grade, HAF grade, MAF grade, FEF grade, GPF grade, SRF grade, FT grade, and MT grade.

[0033] From the viewpoint of adhesion to the adhesive layer, the filler is preferably a filler containing carbon black, but the filler may consist of only carbon black. The amount of the filler is usually in the range of 10 to 150 parts by mass, and preferably in the range of 20 to 100 parts by mass, based on 100 parts by mass of the rubber component (A). The amount of the filler may be in the range of 25 to 80 parts by mass, or in the range of 30 to 70 parts by mass, based on 100 parts by mass of the rubber component (A).

[0034] Cross-linking agent As the crosslinking agent, organic peroxides are preferred, and those having a one-hour half-life temperature of 160° C. or less are preferred. Examples of organic peroxides include dialkyl peroxides, peroxyketals, peroxyesters, ketone peroxides, diacyl peroxides, and peroxydicarbonates. These are used alone or in combination of two or more. Among these, it is preferred to use at least one from the group consisting of dialkyl peroxides, peroxyketals, and peroxyesters having a one-hour half-life temperature of 100 to 160° C., and it is particularly preferred to use at least one from the group consisting of dialkyl peroxides, peroxyketals, and peroxyesters having a one-hour half-life temperature of 110 to 160° C., because the rubber composition kneaded with the crosslinking agent has excellent scorch resistance and reactivity with adhesives.

[0035] Here, "half-life" refers to the time it takes for the concentration of the organic peroxide to become half of its initial value. Therefore, the "half-life temperature" is an index that indicates the decomposition temperature of the organic peroxide. The above "one-hour half-life temperature" is the temperature at which the half-life is one hour. In other words, the lower the one-hour half-life temperature, the easier it is to decompose at low temperatures and the faster the reaction rate. If the one-hour half-life temperature is too low, scorching is more likely to occur and it becomes difficult to react with adhesives.

[0036] Examples of dialkyl peroxides include di(2-t-butylperoxypropyl)benzene, dicumyl peroxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, t-butylcumyl peroxide, di-t-hexyl peroxide, di-t-butyl peroxide, and 2,5-dimethyl-2,5-di(t-butylperoxy)hexyne-3.

[0037] Examples of peroxyketals include n-butyl-4,4-di(t-butylperoxy)valerate, 2,2-di(t-butylperoxy)butane, 2,2-di(4,4-di(t-butylperoxy)cyclohexyl)propane, 1,1-di(t-butylperoxy)cyclohexane, 1,1-di(t-hexylperoxy)cyclohexane, 1,1-di(t-hexylperoxy)-3,3,5-trimethylcyclohexane, and 1,1-di(t-butylperoxy)-2-methylcyclohexane.

[0038] Examples of peroxyesters include t-butyl peroxybenzoate, t-butyl peroxyacetate, t-propyl peroxyacetate, t-hexyl peroxybenzoate, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, t-butylperoxy-2-ethylhexyl monocarbonate, t-butyl peroxylaurate, t-butylperoxyisopropyl monocarbonate, t-butylperoxy-3,5,5-trimethylhexanoate, t-butylperoxymaleic acid, and t-hexylperoxyisopropyl monocarbonate.

[0039] Among these, 1,1-di(t-hexylperoxy)cyclohexane, 1,1-di(t-butylperoxy)cyclohexane, n-butyl-4,4-di(t-butylperoxy)valerate, 2,2-di(t-butylperoxy)butane, t-butylperoxybenzoate, t-butylperoxy-2-ethylhexyl monocarbonate, t-hexylperoxybenzoate, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, di(2-t-butylperoxypropyl)benzene, dicumyl peroxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, t-butylcumyl peroxide, di-t-hexyl peroxide, di-t-butyl peroxide, and 2,5-dimethyl-2,5-di(t-butylperoxy)hexyne-3 are preferred because of their high reactivity with the rubber component (A). Particularly preferred are 1,1-di(t-butylperoxy)cyclohexane, n-butyl-4,4-di(t-butylperoxy)valerate, 1,1-di(t-hexylperoxy)cyclohexane, t-hexylperoxybenzoate, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, di(2-t-butylperoxypropyl)benzene, dicumyl peroxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, and t-butylcumyl peroxide.

[0040] The amount of the crosslinking agent (in the case of a raw material with a purity of 100%) is preferably, for example, in the range of 0.4 to 12 parts by mass per 100 parts by mass of the rubber component (A). If the amount of the crosslinking agent is too small, it tends to be difficult to sufficiently proceed with the crosslinking reaction, whereas if the amount of the crosslinking agent is too large, the crosslinking density increases rapidly during the crosslinking reaction, which tends to reduce the adhesive strength. When a pure organic peroxide having a purity of 100% is not used, the organic peroxide is blended so that the ratio calculated as the pure organic peroxide falls within the above range.

[0041] Cross-linking aid Examples of crosslinking aids include maleimide compounds, triallyl cyanurate (TAC), triallyl isocyanurate (TAIC), trimethylolpropane trimethacrylate (TMPT), bifunctional (meth)acrylates, 1,2-polybutadiene, etc. These are used alone or in combination of two or more. Among these, it is preferable to use maleimide compounds and TAIC because they have a large effect of improving crosslink density and strength.

[0042] The amount of the crosslinking aid is preferably 5 parts by mass or less based on 100 parts by mass of the rubber component (A). If the amount of the crosslinking aid is too large, the crosslink density increases rapidly during the crosslinking reaction, and the tensile elongation and adhesive strength tend to decrease.

[0043] Anti-aging agent Examples of the anti-aging agent include amine-based, phenol-based, imidazole-based, phosphoric acid-based, wax, etc. These may be used alone or in combination of two or more kinds. Specifically, for example, amine-based antioxidants such as N-phenyl-1-naphthylamine, N,N'-diphenyl-p-phenylenediamine, N,N'-di-2-naphthyl-p-phenylenediamine, N-phenyl-N'-isopropyl-p-phenylenediamine, di(4-octylphenyl)amine, 4,4'-bis(α,α-dimethylbenzyl)diphenylamine, p-(p-toluenesulfonylamido)diphenylamine, and N-phenyl-N'-(1,3-dimethylbutyl)-p-phenylenediamine; 2,6-di-t-butyl-4-methylphenol, 2,6-di-t-butyl-4-ethylphenol, 2,6-di-t-butylphenol, 2,4,6-tri-t-butylphenol, styrenated phenol, Examples of antioxidants include phenol-based antioxidants such as phenol, 2,2'-methylenebis(4-methyl-6-t-butylphenol), 2,2'-methylenebis(4-ethyl-6-t-butylphenol), 4,4'-thiobis(3-methyl-6-t-butylphenol), 4,4'-butylidenebis(3-methyl-6-t-butylphenol), 4,4'-methylenebis(2,6-t-butylphenol), 4,4'-isopropylidenebis(2,6-di-t-butylphenol), and 2,2'-isobutylidenebis(4,6-dimethylphenol); and imidazole-based antioxidants such as 2-mercaptobenzimidazole, 2-mercaptobenzimidazole zinc salt, and 2-mercaptomethylbenzimidazole.

[0044] The blending amount of the antioxidant is usually within a range of 0.1 to 10 parts by mass based on 100 parts by mass of the rubber component (A). The blending amount of the antioxidant can be appropriately set within the above range, and may be, for example, 1 to 8 parts by mass, 2 to 6 parts by mass, etc.

[0045] The rubber composition may contain an adhesive component (such as a silane coupling agent), but it is preferable not to contain it (not to contain it) from the viewpoint of improving releasability when molding the seal member with a mold. Therefore, the amount of the adhesive component (such as a silane coupling agent) is preferably less than 0.1 mass % of the entire rubber composition, preferably less than 0.01 mass %, and more preferably 0 mass %.

[0046] Preparation of Rubber Composition The present rubber composition for forming the above-mentioned seal member is prepared by kneading the rubber component (A) and, as necessary, various additives such as a plasticizer, a filler, an organic peroxide (crosslinking agent), a crosslinking aid, an antioxidant, a processing aid, etc., with a roll, a kneader, a Banbury mixer, etc. As described later, the present rubber composition is molded in a mold, press molded, etc., to form a seal member of a predetermined thickness.

[0047] <Adhesive layer> Next, the adhesive layer that bonds the sealing member made of the rubber composition to the substrate will be described. It is important to use an adhesive containing the following components (α) and (β) as the adhesive that forms the adhesive layer. With an adhesive containing only one of the following components (α) and (β), it tends to be difficult to improve the acid-resistant adhesion between the sealing member and the substrate under high temperature and long-term conditions.

[0048] <Silane coupling agent (α)> The component (α) is a copolymer oligomer type silane coupling agent having a hydrophilic functional group and a hydrophobic functional group, wherein the hydrophilic functional group is the following (a) and the hydrophobic functional group is the following (b), and the molar ratio (Ma / Mb) of the amount of substance Ma (mol) of the hydrophilic functional group to the amount of substance Mb (mol) of the hydrophobic functional group contained in 1 mole of the molecule is 0.33 to 3.00. (a) At least one selected from the group consisting of a silanol group, an alkoxy group, an amino group, an isocyanate group, an epoxy group, a ureido group, a carboxy group, and a hydroxy group, and contains at least a silanol group or an alkoxy group. (b) At least one selected from the group consisting of a vinyl group, a (meth)acryloyl group, a maleimide group, a methyl group, an ethyl group, a styryl group, a phenyl group, and a mercapto group.

[0049] As described above, the silane coupling agent shown in (α) has one or more types of hydrophilic functional groups shown in (a) (however, a silanol group or an alkoxy group is essential, and the others are optional), and also has one or more types of hydrophobic functional groups shown in (b). From the viewpoint of reactivity with the base material and reactivity with the sealing member, among the hydrophilic functional groups shown in (a), a silanol group (a hydroxy group constituting a silanol structure), an alkoxy group, an amino group, and an isocyanate group are preferred, and a silanol group, an alkoxy group, and an amino group are more preferred. In addition, from the viewpoint of reactivity with the rubber component, the crosslinking agent, and the crosslinking aid in the seal member, among the hydrophobic functional groups shown in (b), a vinyl group, a (meth)acryloyl group, and a maleimide group are preferred, and a vinyl group is more preferred.

[0050] In addition, in order to obtain acid-resistant adhesion, particularly acid-resistant adhesion under high temperature and long-term conditions, the silane coupling agent shown in (α) must have a molar ratio (Ma / Mb) of the amount of hydrophilic functional groups contained in one mole of the molecule to the amount of hydrophobic functional groups contained in one mole of the molecule, Ma (moles), of 0.33 to 3.00. From the same viewpoint, the molar ratio (Ma / Mb) is preferably in the range of 0.40 to 2.90, and more preferably in the range of 0.45 to 2.75. The molar ratio (Ma / Mb) may also be in the range of 0.45 to 2.0.

[0051] Furthermore, the silane coupling agent shown in (α) is of the copolymer oligomer type, that is, a copolymer oligomer, from the viewpoint of film-forming properties, etc. That is, the silane coupling agent shown in (α) can be obtained by subjecting the silane coupling agent having each functional group shown in (a) or (b) to an oligomerization reaction.

[0052] Among the silane coupling agents having a hydrophilic functional group shown in (a), examples of the silane coupling agent having a hydrophilic functional group other than a silanol group and an alkoxy group include 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylidene)propylamine, 3-isocyanatepropyltriethoxysilane, 3-ureidopropyltrialkoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-carboxypropyltrimethoxysilane, 3-carboxypropyltriethoxysilane, 3-hydroxypropyltrimethoxysilane, and 3-hydroxypropyltriethoxysilane. These may be used alone or in combination of two or more. Of these, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, and 3-isocyanatepropyltriethoxysilane are preferred.

[0053] Examples of the silane coupling agent having a hydrophobic functional group shown in (b) include vinyltrimethoxysilane, vinyltriethoxysilane, 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, N-(trimethoxysilylpropyl)maleimide, N-(triethoxysilylpropyl)maleimide, p-styryltrimethoxysilane, p-styryltriethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, 3-mercaptopropylmethyltrimethoxysilane, 3-mercaptopropylmethyltriethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, n-propyltrimethoxysilane, n-propyltriethoxysilane, etc. These may be used alone or in combination of two or more. Of these, vinyltrimethoxysilane, vinyltriethoxysilane, 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, N-(trimethoxysilylpropyl)maleimide, and N-(triethoxysilylpropyl)maleimide are preferred.

[0054] In the oligomerization reaction, for example, 0.5 to 2.0 moles of a silane coupling agent having no hydrophobic functional group but having a hydrophilic functional group as shown in (a) is used for 1.0 mole of a silane coupling agent having a hydrophobic functional group as shown in (b). In addition, 0.2 to 5.0 moles of water for hydrolysis is used for 1 mole of the total amount of substances of the silane coupling agent having a hydrophilic functional group as shown in (a) and the silane coupling agent having a hydrophobic functional group as shown in (b). In addition, among the silane coupling agents having a hydrophilic functional group as shown in (a), silane coupling agents having hydrophilic functional groups other than silanol groups and alkoxy groups may not necessarily be included. The oligomerization reaction is carried out by feeding the above-mentioned raw materials into a reactor having a distillation apparatus and a stirrer and stirring at about 60°C for about 1 hour. After that, about 0.5 to 2.0 moles of an acid such as formic acid is added within 1 hour to 1 mole of the total amount of substances of the silane coupling agent having a hydrophilic functional group shown in (a) and the silane coupling agent having a hydrophobic functional group shown in (b). The temperature at this time is kept at about 65°C. The reaction is further stirred for 1 to 5 hours to proceed, and at the same time, the alcohol generated by hydrolysis is distilled under reduced pressure. The distillation is stopped when only water remains in the distilled water, and then the silane concentration is adjusted by dilution to a range of 30 to 80 mass%, thereby obtaining a copolymerized oligomer (silane coupling agent (α)). This copolymerized oligomer is an oligomer that is soluble in an alcohol-based organic solvent such as methanol or ethanol. The copolymerized oligomer is preferably a trimer or more from the viewpoint of increasing the film-forming property, water resistance, and acid resistance when applying the adhesive.

[0055] In addition, as the adhesive containing the copolymer oligomer, a commercially available product can be used as it is. Specific examples include CHEMLOK5151 manufactured by Lord Far East Co., Ltd. [the molar ratio (Ma / Mb) of the amount of substance of hydrophilic functional groups to the amount of substance of hydrophobic functional groups contained in 1 mole of the copolymer oligomer to be 1.13], MEGUM3290 manufactured by Dow Chemical Co., Ltd. [the molar ratio (Ma / Mb) of the amount of substance of hydrophilic functional groups to the amount of substance of hydrophobic functional groups contained in 1 mole of the copolymer oligomer to be 2.70], and X-12-1048 manufactured by Shin-Etsu Chemical Co., Ltd. [the molar ratio (Ma / Mb) of the amount of substance of hydrophilic functional groups to the amount of substance of hydrophobic functional groups contained in 1 mole of the copolymer oligomer to be 2.70]. Examples of such copolymers include X-12-1050 manufactured by Shin-Etsu Chemical Co., Ltd. (a molar ratio of the amount of substance Ma (mol) of hydrophilic functional groups to the amount of substance Mb (mol) of hydrophilic functional groups contained in 1 mole of the copolymer oligomer (Ma / Mb): 1.67), and KR-513 manufactured by Shin-Etsu Chemical Co., Ltd. (a molar ratio of the amount of substance Ma (mol) of hydrophilic functional groups to the amount of substance Mb (mol) of hydrophobic functional groups contained in 1 mole of the copolymer oligomer (Ma / Mb): 0.49).

[0056] 《Organic titanate compounds (β)》 The component (β) is a component that constitutes the adhesive together with the component (α) and is used to improve acid-resistant adhesion, particularly acid-resistant adhesion between a substrate and a sealing member under high-temperature and long-term conditions. As the organic titanate compound (β), it is preferable to use at least one selected from the group consisting of titanium alkoxide, titanium chelate, and titanium acylate.

[0057] Examples of titanium alkoxides include tetramethyl titanate, tetraethyl titanate, tetra-normal propyl titanate, tetraisopropyl titanate, tetra-normal butyl titanate, tetraisobutyl titanate, tetra-t-butyl titanate, tetraoctyl titanate, tetrastearyl titanate, tetra(2-ethylhexyl) titanate, tetramethyl titanate, etc. Among these, tetraisopropyl titanate, tetra-normal butyl titanate, and tetrastearyl titanate are preferred.

[0058] Examples of titanium chelates include titanium acetylacetonate, titanium octylene glycolate, titanium tetraacetylacetonate, titanium ethylacetoacetate, titanium triethanolaluminate, etc. Among these, titanium acetylacetonate and titanium ethylacetoacetate are preferred.

[0059] Examples of titanium acylate include titanium isostearate, tri-n-butoxy titanium monostearate, di-i-propoxy titanium distearate, titanium stearate, di-i-propoxy titanium diisostearate, (2-n-butoxycarbonylbenzoyloxy)tributoxy titanium, etc. Among these, titanium stearate is preferred.

[0060] Among these organic titanate compounds (β), from the viewpoint of further improving acid-resistant adhesion, particularly acid-resistant adhesion between a substrate and a sealing member under high-temperature and long-term conditions, titanium alkoxides and titanium chelates are preferred, and titanium alkoxides are more preferred.

[0061] Among titanium alkoxides, from the viewpoint of solubility and hydrolysis, R 1 Titanium alkoxides in which the alkyl group represented by the following formula (I) has 1 to 18 carbon atoms are preferred, and titanium alkoxides in which the alkyl group has 2 to 10 carbon atoms are more preferred. Formula: Ti(OR 1 ) 4 (1) [In formula (1), R 1 each independently represents the same or different alkyl group.

[0062] R in (1) above 1 Specific examples of the alkyl group include a methyl group, an ethyl group, a propyl group, an isopropyl group, an n-butyl group, a sec-butyl group, a t-butyl group, an n-pentyl group, an n-hexyl group, an n-heptyl group, an n-octyl group, a 2-ethylhexyl group, a stearyl group, and an isostearyl group.

[0063] From the viewpoint of acid-resistant adhesion, particularly acid-resistant adhesion under high-temperature and long-term conditions, the blending amount of component (β) is preferably 0.5 part by mass or more, more preferably 1 to 200 parts by mass, even more preferably 3 to 200 parts by mass, and particularly preferably 5 to 200 parts by mass, per 100 parts by mass of component (α). If the amount of component (β) is outside the above range, the acid-resistant adhesion under high-temperature, long-term conditions tends to be insufficient. The blending amount of the (β) component can be appropriately set within the above range, and may be, for example, in the range of 10 to 150 parts by mass, 30 to 120 parts by mass, or 35 to 70 parts by mass per 100 parts by mass of the (α) component.

[0064] In addition to the components (α) and (β), the adhesive forming the adhesive layer may contain phenolic resin, bismaleimide resin, vinyl resin, etc., for the purpose of increasing adhesion to the substrate and ensuring hydrophobicity to prevent water from penetrating the adhesive layer and improving water resistance and acid resistance. However, it is preferable that the adhesive contains the components (α) and (β) as main components. The above "main component" refers to the main component of the adhesive, and means that the total amount of the (α) and (β) components is 50% by mass or more of the adhesive (excluding the solvent). The total amount of the (α) and (β) components can be appropriately adjusted within the above range, and may be, for example, 60% by mass or more, 70% by mass or more, 80% by mass or more, 90% by mass or more, or even 100% by mass of the adhesive (excluding the solvent).

[0065] The adhesive forming the adhesive layer is usually used as a solution diluted with an organic solvent so that the total amount of the silane coupling agent shown in (α) and the organic titanate compound shown in (β) is about 0.5 to 25 mass %. Examples of the organic solvent include alcohol-based organic solvents such as methanol, ethanol, butoxyethanol, isopropanol, and 2-ethoxyethanol (ethylene glycol monoethyl ether), ketone-based organic solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and acetylacetone, and hydrocarbon-based solvents such as xylene and toluene.

[0066] <Base material> Next, the substrate will be described. Examples of the material of the substrate include stainless steel, titanium, copper, magnesium, aluminum, carbon, graphite, conductive resin (thermoplastic resin or thermosetting resin mixed with graphite, polyacrylonitrile carbon fiber, etc.), etc. Among these, substrates made of stainless steel, titanium (pure titanium or titanium alloy), and conductive resin are preferred from the viewpoint of acid resistance. Furthermore, from the viewpoint of providing a fuel cell laminate having excellent acid resistance and adhesiveness, it is preferred to use a substrate made of austenitic stainless steel. Specific examples of austenitic stainless steel include SUS304, SUS301, SUS316L, etc.

[0067] From the viewpoint of acid resistance, it is effective to use a substrate made of stainless steel, particularly a substrate made of austenitic stainless steel, but such a substrate has a problem in that it is difficult to adhere to. Therefore, for example, when only a silane coupling agent (α) is used as an adhesive, there is room for improvement in acid-resistant adhesion under high temperature and long-term conditions, but when an organic titanate compound (β) is further blended as a constituent component of the adhesive as in the present invention, it can be said to be excellent in that it can satisfy acid-resistant adhesion even when a substrate made of stainless steel, particularly austenitic stainless steel, is used as the substrate.

[0068] From the viewpoint of electrical conduction reliability, the surface of the substrate made of the above-mentioned material may have a carbon thin film, such as a DLC film (diamond-like carbon film) or a graphite film, formed by a process such as a PVD method (physical vapor deposition), a CVD method (chemical vapor deposition), etc. The thickness of the carbon thin film is preferably 10 to 500 nm.

[0069] <Method of manufacturing laminate> Next, a method for producing the present fuel cell laminate will be described. First, the present rubber composition for forming a seal member is prepared as described above, and then the present rubber composition is molded in a mold, pressed, or the like to produce a flat rubber member having a predetermined thickness. The flat rubber member may be either crosslinked or uncrosslinked, but from the viewpoint of enhancing adhesiveness, the uncrosslinked one is preferred. Then, an adhesive containing a silane coupling agent (α) and an organic titanate compound (β) is applied onto a substrate such as a stainless steel plate by any method such as spraying, dipping, or roll coating, and then dried at room temperature if necessary. The flat rubber member is then laminated onto the surface, and crosslinked and bonded under specified conditions (such as 130 to 200°C for 3 to 30 minutes), thereby producing a laminate in which the substrate and the crosslinked rubber member (sealing member) are bonded together. It is preferable that the crosslinked rubber member be molded in advance into a predetermined shape according to the shape of the sealing portion, since this eliminates the need for complicated positioning, facilitates continuous processing, and improves productivity. The crosslinked rubber member may be formed by crosslinking the rubber composition prepared above on a substrate coated with the adhesive using a predetermined mold, thereby making the crosslinked adhesion stronger.

[0070] The thickness of each member in the present fuel cell laminate varies depending on the sealing portion where the laminate is used, but for example, the thickness of the base material is usually in the range of 0.05 to 5 mm, preferably in the range of 0.1 to 3 mm. The thickness of the sealing member is usually in the range of 0.2 to 5 mm, preferably in the range of 0.5 to 3 mm. The thickness of the adhesive layer is usually 1×10 -5 ~0.025mm range, preferably 2×10 -5 The thickness of the adhesive layer is in the range of 0.002 mm to 1.0 mm. Although the adhesive layer may be multi-layered, consisting of two or more layers, a single layer is preferred in terms of shortening the coating process time.

[0071] <Fuel cell component parts> The fuel cell laminate is used as a component of a fuel cell. Examples of fuel cell constituent members include laminates in which a fuel cell base material and a sealing member for sealing the base material are bonded via an adhesive layer.

[0072] The substrate for the fuel cell varies depending on the type and structure of the fuel cell, but examples include a separator, a gas diffusion layer (GDL), and an MEA (membrane electrolyte, electrode). The separator may be made of a metal such as stainless steel (SUS304, etc.) or titanium, or a conductive resin (a thermoplastic resin or a thermosetting resin mixed with graphite, polyacrylonitrile carbon fiber, etc.). The separator may have a carbon thin film such as a DLC film or a graphite film formed by a process such as a PVD method or a CVD method on the surface of the separator made of the above metals. Examples of fuel cells to which the present invention can be applied include polymer electrolyte fuel cells (PEFCs) (including direct methanol fuel cells (DMFCs)).

[0073] An example of the fuel cell laminate is shown in Fig. 1. Fig. 1 shows a member in which a lip 4b having a rectangular cross section and a convex shape is provided on the periphery of a separator 5 having a rectangular thin plate shape and a cross section with a total of six grooves extending in the longitudinal direction, via an adhesive layer 6. The lip 4b is a sealing member made of the rubber composition containing the rubber component (A), and the adhesive layer 6 is made of an adhesive containing a silane coupling agent (α) and an organic titanate compound (β).

[0074] <Fuel cell seal body> Next, an example of a fuel cell seal using the fuel cell laminate according to the present invention is shown in Fig. 2. Fig. 2 mainly shows a single cell 1 in a fuel cell formed by stacking a plurality of cells, and the cell 1 includes an MEA 2, a gas diffusion layer (GDL) 3, a seal member 4, a separator 5, and an adhesive layer 6. The seal member 4 is made of the present rubber composition containing the rubber component (A), and the adhesive layer 6 is made of an adhesive containing a silane coupling agent (α) and an organic titanate compound (β).

[0075] Examples of the above fuel cell seal body include, as shown in FIG. 2, one in which a separator 5 and a seal member 4 are bonded via an adhesive layer 6, one in which an MEA 2 and a seal member 4 are bonded via an adhesive layer 6, and one in which a gas diffusion layer 3 and a seal member 4 are bonded via an adhesive layer 6. The adhesive layer 6' that bonds adjacent sealing members 4 together may be a layer made of an adhesive containing a silane coupling agent (α) and an organic titanate compound (β), but may also be an adhesive layer made of, for example, rubber cement or a rubber composition that is liquid at room temperature (23°C) (liquid ethylene propylene rubber (liquid EPM), liquid EPDM, liquid acrylonitrile-butadiene rubber (liquid NBR), liquid hydrogenated acrylonitrile-butadiene rubber (liquid H-NBR), etc.).

[0076] Although not shown, the MEA 2 is composed of an electrolyte membrane and a pair of electrodes arranged on both sides of the electrolyte membrane in the stacking direction. The electrolyte membrane and the pair of electrodes have a rectangular thin plate shape. Gas diffusion layers 3 are arranged on both sides of the MEA 2 in the stacking direction. The gas diffusion layers 3 are porous layers and have a rectangular thin plate shape.

[0077] The separator 5 is made of titanium and has a rectangular thin plate shape with a total of six grooves extending in the longitudinal direction, which give the separator 5 a corrugated cross section. The separators 5 are disposed opposite each other in the stacking direction of the gas diffusion layer 3. Between the gas diffusion layer 3 and the separator 5, gas flow paths 7 for supplying gas to the electrodes are defined by utilizing the corrugated shape.

[0078] The sealing member 4 has a rectangular frame shape. The sealing member 4 is adhered to the periphery of the MEA 2 and the gas diffusion layer 3, and to the separator 5 via an adhesive layer 6, and seals the periphery of the MEA 2 and the gas diffusion layer 3. In the example of Fig. 2, the sealing member 4 is made up of two separate members, an upper member and a lower member, but it may be a single sealing member combining the two.

[0079] When a fuel cell such as a solid polymer fuel cell is in operation, a fuel gas and an oxidant gas are each supplied through the gas flow passage 7. Here, the periphery of the MEA 2 is sealed by the sealing member 4 via the adhesive layer 6. Therefore, mixing and leakage of the gases does not occur.

[0080] <Fuel cells and the like including laminates for fuel cells> One embodiment of the present invention includes a fuel cell including the fuel cell laminate, and a fuel cell vehicle (FVC) including the fuel cell. That is, one embodiment of the present invention is a fuel cell including a laminate for a fuel cell in which a substrate and a sealing member are bonded via an adhesive layer, the sealing member being made of the present rubber composition containing component (A), and the adhesive layer being made of an adhesive containing components (α) and (β). Furthermore, one embodiment of the present invention is a fuel cell vehicle (FVC) equipped with a fuel cell including a laminate for a fuel cell in which a substrate and a sealing member are bonded via an adhesive layer, the sealing member being made of the present rubber composition containing component (A), and the adhesive layer being made of an adhesive containing components (α) and (β). EXAMPLES

[0081] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to the following examples as long as it does not depart from the gist of the present invention.

[0082] First, the following rubber compositions, adhesives, and substrates were prepared.

[0083] <Rubber composition> <Rubber composition (R1)> 100 parts by mass of ethylene-butene-diene rubber (Mitsui Chemicals, Inc., EBT-K-9330M), 1 part by mass of antioxidant (Ouchi Shinko Chemical Industry, Nocrac NS-5), 50 parts by mass of carbon black (Tokai Carbon, FEF-grade carbon black, Seast SO), and 15 parts by mass of plasticizer (Nippon Steel Chemical & Material, poly-α-olefin, PAO601) were kneaded for 5 minutes at 120 ° C. using a Banbury mixer. After cooling the kneaded product, 6 parts by mass of crosslinking agent (NOF Corporation, Perhexa C-80) was added, and the mixture was further kneaded for 10 minutes at 50 ° C. using an open roll to prepare a rubber composition (R1).

[0084] <Rubber composition (R2)> Rubber composition (R2) was prepared in the same manner as rubber composition (R1), except that ethylene-butene-diene rubber (manufactured by Mitsui Chemicals, Inc., EBT-K-9330M) was replaced with ethylene-propylene-diene rubber (manufactured by Mitsui Chemicals, Inc., EPT-9090M).

[0085] <Rubber composition (R3)> Rubber composition (R3) was prepared in the same manner as rubber composition (R1), except that ethylene-butene-diene rubber (EBT-K-9330M, manufactured by Mitsui Chemicals) was replaced with ethylene-propylene-diene rubber (Esprene 5361, manufactured by Sumitomo Chemical).

[0086] <Adhesive> The adhesive materials shown below were prepared.

[0087] <Silane coupling agent (α1)> 100 parts by mass of vinyltrimethoxysilane, 68.4 parts by mass of 3-aminopropyltrimethoxysilane, and 33.1 parts by mass of water (1.74 moles per mole of the total amount of the silane coupling agents) were charged into a reactor equipped with a distillation apparatus and a stirrer, and stirred at about 60°C for about 1 hour. Then, an acid such as formic acid was added within 1 hour so that the amount added was about 0.5 to 2.0 moles per mole of the total amount of the silane coupling agents. The temperature at this time was kept at about 65°C. The reaction was allowed to proceed for another 1 to 5 hours by stirring, and at the same time, the alcohol generated by hydrolysis was distilled under reduced pressure. The distillation was stopped when only water remained in the distilled water, and then the silane concentration was adjusted by dilution to 30 to 80% by mass, thereby obtaining a copolymer oligomer having a molar ratio (Ma / Mb) of 1.17 of the amount of substance Ma (mol) of hydrophilic functional groups to the amount of substance Mb (mol) of hydrophobic functional groups contained in 1 mole of the molecule. The hydrophobic functional group is a vinyl group, and the hydrophilic functional group is a silanol group, an alkoxy group, or an amino group.

[0088] <Silane coupling agent (α2)> X-12-1050 manufactured by Shin-Etsu Chemical Co., Ltd. (The molar ratio (Ma / Mb) of the amount of hydrophilic functional groups Ma (moles) to the amount of hydrophobic functional groups Mb (moles) contained in 1 mole of the copolymer oligomer is 1.67, the hydrophobic functional groups are acryloyl groups, and the hydrophilic functional groups are silanol groups and alkoxy groups.)

[0089] <Silane coupling agent (α3)> KR-513 manufactured by Shin-Etsu Chemical Co., Ltd. (The molar ratio (Ma / Mb) of the amount of hydrophilic functional groups Ma (mol) to the amount of hydrophobic functional groups Mb (mol) contained in 1 mol of the copolymer oligomer is 0.49, the hydrophobic functional groups are acryloyl groups and methyl groups, and the hydrophilic functional groups are silanol groups and alkoxy groups.)

[0090] <Silane coupling agent (α'1)> X-12-972F manufactured by Shin-Etsu Chemical Co., Ltd. (The functional groups in the copolymer oligomer are only hydrophilic functional groups. The hydrophilic functional groups are silanol groups, alkoxy groups, and amino groups.)

[0091] <Silane coupling agent (α'2)> X-24-9590 manufactured by Shin-Etsu Chemical Co., Ltd. (The functional groups in the copolymer oligomer are only hydrophilic functional groups. The hydrophilic functional groups are silanol groups, alkoxy groups, and amino groups.)

[0092] Titanium alkoxide (β1-1) Tetraisopropyl titanate (A-1, manufactured by Nippon Soda Co., Ltd.)

[0093] Titanium alkoxide (β1-2) Tetra-normal butyl titanate (Nippon Soda Co., Ltd., B-1)

[0094] Titanium alkoxide (β1-3) Tetrastearyl titanate (Matsumoto Fine Chemicals, Orgatics TA-90)

[0095] Titanium acylate (β2) Titanium stearate (Nippon Soda Co., Ltd., S-151)

[0096] Titanium chelate (β3-1) Titanium acetylacetonate (Matsumoto Fine Chemicals, Orgatics TC-100)

[0097] Titanium chelate (β3-2) Titanium ethyl acetoacetate (Matsumoto Fine Chemicals, Orgatics TC-710)

[0098] Inorganic titanate compounds (β'1) Titanium oxide (Sakai Chemical Industry Co., Ltd., SSP-M)

[0099] Inorganic titanate compounds (β'2) Titanium oxide (Sakai Chemical Industry Co., Ltd., STR-100N)

[0100] <Base material> The following substrates were prepared. SUS(1) Stainless steel (SUS304) base material (width 25 mm, length 60 mm, thickness 1.5 mm)

[0101] SUS(2) Stainless steel (SUS316) base material (width 25 mm, length 60 mm, thickness 1.5 mm)

[0102] Example 1 A ratio of 100 parts by mass of silane coupling agent (α1) to 0.5 parts by mass of titanium alkoxide (β1-1) was mixed and diluted with an alcohol-based organic solvent containing ethanol and butoxyethanol to prepare an adhesive with a solids concentration of 10% by mass (an adhesive with a total blend of silane coupling agent (α1) and titanium alkoxide (β1-1) of 10% by mass, ethanol of 85% by mass, and butoxyethanol of 5% by mass). SUS (1) was prepared as a substrate, and the adhesive prepared above was spray-coated on the surface of the substrate within the range specified by JIS K 6256-2 so that the thickness after application was about 0.5 μm. Thereafter, the rubber composition (R1) and the substrate were crosslinked and bonded by holding them at 170° C. for 15 minutes using a specified mold so that the shape conformed to JIS K 6256-2, and an adhesion evaluation sample (laminate) was produced in which a rubber molded body (sealing member) with a thickness of 2.0 mm and the substrate were bonded via an adhesive layer (thickness 0.5 μm).

[0103] [Examples 2 to 15, Comparative Examples 1 to 7] Adhesion evaluation samples (laminates) for Examples 2 to 15 and Comparative Examples 1 to 7 were prepared in the same manner as in Example 1, except that the type of rubber composition, the type and compounding ratio of the silane coupling agent and titanate compound, and the type of substrate were changed as shown in Tables 1 and 2. For example, in the case of Example 2, an adhesion evaluation sample (laminate) was prepared as follows. A mixture of 100 parts by mass of silane coupling agent (α1) and 5 parts by mass of titanium alkoxide (β1-1) was diluted with an alcohol-based organic solvent containing ethanol and butoxyethanol to prepare an adhesive with a solids concentration of 10% by mass (an adhesive with a total blend of silane coupling agent (α1) and titanium alkoxide (β1-1) of 10% by mass, ethanol of 85% by mass, and butoxyethanol of 5% by mass). SUS (1) was prepared as a substrate, and the adhesive prepared above was spray-coated on the surface of the substrate within the range specified by JIS K 6256-2 so that the thickness after application was about 0.5 μm. Thereafter, the rubber composition (R1) and the substrate were crosslinked and bonded by holding them at 170° C. for 15 minutes using a specified mold so that the shape conformed to JIS K 6256-2, and an adhesion evaluation sample (laminate) was produced in which a rubber molded body (sealing member) with a thickness of 2.0 mm and the substrate were bonded via an adhesive layer (thickness 0.5 μm).

[0104] The adhesion evaluation samples (laminates) of the examples and comparative examples thus obtained were evaluated for their properties according to the following criteria. The results are shown in Tables 1 to 3 below.

[0105] <Initial adhesion evaluation test> The adhesion evaluation samples (laminates) obtained as described above were subjected to a 90° peel test specified in JIS K6256-2 (2006) under a room temperature (23°C) environment, and were visually observed to evaluate the adhesion between the substrate and the rubber molded body (sealing member) in each adhesion evaluation sample (laminate) according to the following criteria. The results are shown in Tables 1 and 2. (Evaluation Criteria) ◯: Material destruction occurred in the rubber molding (sealing member). ×: No material destruction occurred in the rubber molded body (sealing member).

[0106] <Evaluation test of acid resistance under high temperature and long-term conditions (1)> The adhesion evaluation samples (laminates) of the examples and comparative examples were placed in an aqueous sulfuric acid solution adjusted to pH 3.0, and immersed in the aqueous sulfuric acid solution at 120° C. for 336 hours (or 672 hours). The adhesion evaluation sample was then removed from the sulfuric acid aqueous solution and left for one day, after which a 90° peel test was carried out in accordance with JIS K 6256-2 (2006), and the sample was visually observed and evaluated according to the following criteria. The results are shown in Tables 1 and 2. In addition, "-" in the evaluation column of Table 2 indicates that the initial adhesion evaluation was "x", and therefore the acid-resistant adhesion was not evaluated. (Evaluation Criteria) ◎: The combined percentage of material failure of the rubber molding and cohesive failure of the adhesive layer exceeds 80%. ◯: The total percentage of material failure of the rubber molding and cohesive failure of the adhesive layer is 50 to 80%. Δ: Material failure of the rubber molding and cohesive failure of the adhesive layer were observed, but the total proportion was less than 50%. ×: The rate of interfacial peeling is nearly 100%.

[0107] <Evaluation test of acid resistance under high temperature and long-term conditions (2)> Next, in order to verify the effect of the type of organic titanate compound on the acid resistance, a test was conducted in which the immersion time was extended. Specifically, Examples 3, 8, and 9 are different only in the type of organic titanate compound, with Example 3 using titanium alkoxide, Example 8 using titanium acylate, and Example 9 using titanium chelate. The adhesion evaluation samples (laminates) of Examples 3, 8, and 9 were placed in a sulfuric acid aqueous solution adjusted to pH = 3.0, and immersed in the sulfuric acid aqueous solution at 120 ° C for 840 hours. Thereafter, the adhesion evaluation samples were taken out of the sulfuric acid aqueous solution and left for one day, after which a 90 ° peel test was performed according to JIS K 6256-2 (2006), and the samples were visually observed and evaluated according to the criteria of the above-mentioned <Evaluation test for acid resistance under high temperature and long-term conditions (1)>. The results are shown in Table 3.

[0108] [Table 1]

[0109] [Table 2]

[0110] [Table 3]

[0111] <Results of evaluation test (1) of acid resistance adhesion under high temperature and long-term conditions> From the results in Tables 1 and 2 above, all of the adhesion evaluation samples (laminates) of the examples had good "initial adhesion", and further received excellent ratings in the evaluations of "acid-resistant adhesion at 120°C for 336 hours" and "acid-resistant adhesion at 120°C for 672 hours".

[0112] In contrast, the adhesion evaluation samples (laminates) of Comparative Examples 1 and 2 did not use the organic titanate compound (β) defined in the present invention, and therefore were inferior in the evaluation of "acid-resistant adhesion at 120°C for 336 hours," resulting in unsatisfactory acid-resistant adhesion under high-temperature and long-term conditions.

[0113] The adhesion evaluation sample (laminate) of Comparative Example 3 did not use the silane coupling agent (α) specified in the present invention, and therefore the evaluation result of "initial adhesion" was poor. Specifically, interfacial peeling between the rubber molded body (sealing member) and the adhesive layer was observed, and the adhesiveness was unsatisfactory. Comparative Examples 4 and 5 did not use the silane coupling agent (α) specified in the present invention, but used other silane coupling agents (α'), and therefore the evaluation result of "initial adhesion" was poor. Specifically, interfacial peeling between the rubber molded body (sealing member) and the adhesive layer was observed, and the adhesiveness was unsatisfactory. Thus, it was easily presumed that Comparative Examples 3 to 5 would also have unsatisfactory acid-resistant adhesion under high temperature and long-term conditions, since they were unsatisfactory in initial adhesion.

[0114] In addition, Comparative Examples 6 and 7 did not use the organic titanate compound (β) defined in the present invention, but used an inorganic titanate compound (β'), and therefore were inferior in the evaluation of "acid-resistant adhesion at 120°C for 336 hours", resulting in unsatisfactory acid-resistant adhesion under high temperature and long-term conditions.

[0115] From the above, it was demonstrated that a laminate satisfying the requirements defined in the present invention has excellent initial adhesion and acid resistance under high temperature and long-term conditions.

[0116] <Results of evaluation test (2) of acid resistance adhesion under high temperature and long-term conditions> As shown in Table 1 above, Examples 3, 8, and 9 all have excellent acid-resistant adhesion, but the results in Table 3 above show that Examples 3 and 9 are superior, with Example 3 being particularly excellent. From the above, it has been shown that the use of titanium alkoxides or titanium chelates as the organic titanate compound (β) can further improve acid-resistant adhesion under high-temperature and long-term conditions, and that titanium alkoxides are more preferable than the other. [Industrial Applicability]

[0117] The laminate of the present invention is a laminate in which a sealing member is adhered to a substrate of various kinds via an adhesive layer, and can be suitably used as a laminate for sealing a fuel cell in which a substrate for a fuel cell, such as a metal separator, and a sealing member are adhered to each other via an adhesive layer. [Explanation of symbols]

[0118] 4b Lip (sealing material) 5 Separator (substrate) 6 Adhesive layer

Claims

1. A laminate for a fuel cell, comprising a substrate and a sealing member bonded together via an adhesive layer, The sealing member is made of a rubber composition containing the following component (A), The adhesive layer is made of an adhesive containing the following components (α) and (β): A laminate for a fuel cell. (A) At least one of an ethylene-propylene-diene rubber and an ethylene-butene-diene rubber. (α) A copolymer oligomer type silane coupling agent having a hydrophilic functional group and a hydrophobic functional group, wherein the hydrophilic functional group is the following (a), the hydrophobic functional group is the following (b), and the molar ratio (Ma / Mb) of the amount of substance Ma (mol) of the hydrophilic functional group to the amount of substance Mb (mol) of the hydrophobic functional group contained in 1 mole of the molecule is 0.33 to 3.

00. (a) At least one selected from the group consisting of a silanol group, an alkoxy group, an amino group, an isocyanate group, an epoxy group, a ureido group, a carboxy group, and a hydroxy group, and contains at least a silanol group or an alkoxy group. (b) At least one selected from the group consisting of a vinyl group, a (meth)acryloyl group, a maleimide group, a methyl group, an ethyl group, a styryl group, a phenyl group, and a mercapto group. (β) Organic titanate compounds.

2. 2. The laminate for a fuel cell according to claim 1, wherein the component (β) in the adhesive is at least one of a titanium alkoxide and a titanium chelate.

3. 3. The laminate for a fuel cell according to claim 1, wherein the amount of the component (β) in the adhesive is 0.5 to 200 parts by mass per 100 parts by mass of the component (α).

4. 3. The laminate for a fuel cell according to claim 1, wherein the substrate is made of austenitic stainless steel.

Citation Information

Patent Citations

  • Multilayer body

    WO2022208926A1